Early Modern Women's Writing and the Rhetoric of Modesty - Pender, P. author. aut Link
X, 218 p.
Keywords: An in-depth study of early modern women's modesty rhetoric from the English Reformation to the Restoration. This book provides new readings of modesty's gendered deployment in the works of Anne Askew, Katharine Parr, Mary Sidney, Aemilia Lanyer and Anne Bradstreet.